O noiva: performance e performatividade no retrato - THEISS, Fabricio (2021)
This work seeks to reflect on the construction of male subjectivities from the empirical relationship of my body with the male gender. What draws this relationship and triggers this research is a portrait, entitled The Bride Man, produced by me and an artist friend in 2012 to ritualize my relationship with my partner. This artistic object permeates the creations and events of this research that are reflected in three phases, which I call: PERFORMANCE ONE, PERFORMANCE TWO and PERFORMANCE THREE. In PERFORMANCE ONE, I present the events surrounding the conception of the portrait The bride man and the events that led me to compose two artistic performances: Private Prison, created in 2018; and The Bride Man, created in 2019. PERFORMANCE TWO exposes the creative path of the performative action entitled Smell of Dead Butterflies, in which I dedicated myself to writing and corresponding letters with artists, friends, researchers, strangers, etc., sharing personal happenings and the research reverberations. PERFORMANCE THREE reflects on the unfolding of the performative action Wedding Nights, carried out in the social media application Tinder, through the creation of the Bride, 38 profile. The events narrated during this performative journey were analyzed based on theories involving Gender Studies, Performance Studies and Feminist Theory, dialoguing mainly with the works of the authors Audre Lorde, bell hooks, Eleonora Fabião, Judith Butler, Luciana Lyra, Margareth Rago,Virginie Despentes, Ailton Krenak, Boaventura de Souza Santos, Cassiano Quilici, Michel Foucault, Paul B. Preciado and Richard Schechner. Through the discussions woven around the artistic creations, this research exposes tensions that are implied in normative social practices that aim to maintain patriarchal structures, such as gender and marriage,manufacturers of political fictions that interfere in our ways of being and relating in the world. The field of performing arts is, in this investigation, understood as an infiltration channel for micropolitical actions that generate possible paths for the transformation of the self and of the social daily life.